2011
DOI: 10.2310/8000.2011.100232
|View full text |Cite
|
Sign up to set email alerts
|

Patient safety in emergency medical services: executive summary and recommendations from the Niagara Summit

Abstract: Emergency medical services (EMS) personnel care for patients in challenging and dynamic environments that may contribute to an increased risk for adverse events. However, little is known about the risks to patient safety in the EMS setting. To address this knowledge gap, we conducted a systematic review of the literature, including nonrandomized, noncontrolled studies, conducted qualitative interviews of key informants, and, with the assistance of a pan-Canadian advisory board, hosted a 1-day summit of 52 expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 16 publications
0
41
0
6
Order By: Relevance
“…19,20 There is encouraging attention by the EMS community to enhancing patient safety; in 2010, the National Highway Traffic Safety Administration partnered with the American College of Emergency Physicians to promote an "EMS Culture of Safety," and a 2009 Summit on Patient Safety hosted in partnership with the EMS Chiefs of Canada and the Canadian Patient Safety Institute identified nine strategic priorities to improve patient safety and enhance research activities related to harm reduction and safety. 21 Acting on these priorities will improve the patient safety research enterprise in two ways. First, by encouraging high-quality data reporting and the use of standardized definitions, 22 EMS systems will accumulate data allowing for comparisons within and between systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 There is encouraging attention by the EMS community to enhancing patient safety; in 2010, the National Highway Traffic Safety Administration partnered with the American College of Emergency Physicians to promote an "EMS Culture of Safety," and a 2009 Summit on Patient Safety hosted in partnership with the EMS Chiefs of Canada and the Canadian Patient Safety Institute identified nine strategic priorities to improve patient safety and enhance research activities related to harm reduction and safety. 21 Acting on these priorities will improve the patient safety research enterprise in two ways. First, by encouraging high-quality data reporting and the use of standardized definitions, 22 EMS systems will accumulate data allowing for comparisons within and between systems.…”
Section: Discussionmentioning
confidence: 99%
“…22 Systems and processes must be put in place to better define threats to patient safety specific to EMS, and rigorous research-quality databases are needed to track adverse events in the prehospital setting. 21 As the safety landscape becomes defined, interventions to improve EMS practice can be collaboratively developed, evaluated, and implemented.…”
Section: Discussionmentioning
confidence: 99%
“…Debemos señalar que gran parte de las percepciones positivas obtenidas en nuestros resultados se encuentran moduladas porque los profesionales que trabajan en este ámbito cuentan con una formación específica para el desempeño de su actividad asistencial 28,29 , a diferencia de lo que sucede en otros países donde mayoritariamente la asistencia es realizada por personal paramédico [30][31][32] , que si bien es posible que cuente con un entrenamiento adecuado, no cuenta con la capacitación específica para tomar decisiones clínicas.…”
Section: Discussionunclassified
“…Other benefits of the analysis of the root causes can be named as modifying the deficiencies and using suitable methods which can improve service offering, reducing the costs on the patient and healthcare system as well as improving the output of the medical team in times of crisis all of which result in the accurate identifying the main cause of an incident 12,13 . The results of Sanvl and colleagues 14 and Packstone 15 studies reported that applying the strategy of clear, transparent and implementation procedures are considered to be effective strategies as to prevent medical errors.…”
Section: Discussionmentioning
confidence: 99%